2006
DOI: 10.1002/mds.20920
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic deep brain stimulation in patients with a previous pallidotomy

Abstract: The safety and efficacy of subthalamic nucleus (STN) deep brain stimulation (DBS) in patients who have had a previous unilateral pallidotomy is not clear. We identified 10 patients (9 male) at the Baylor College of Medicine Parkinson's Disease Center who underwent STN DBS after prior unilateral pallidotomy. Demographics, efficacy as determined by off Unified Parkinson's Disease Rating Scale (UPDRS) part III scores, and levodopa equivalent dosing were analyzed. We then compared these to an age- and sex-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
5

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 12 publications
4
16
0
5
Order By: Relevance
“…The reduced motor improvement of STN DBS post pallidotomy found by Ondo et al . (2006) in conjunction with our results and those of Mogilner et al .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The reduced motor improvement of STN DBS post pallidotomy found by Ondo et al . (2006) in conjunction with our results and those of Mogilner et al .…”
Section: Resultsmentioning
confidence: 83%
“…Kleiner‐Fisman et al . (2004) found STN DBS post pallidotomy to be no less efficacious than STN DBS in patients without prior pallidotomy, whereas Ondo et al . (2006) found less motor improvement in patients with prior pallidotomy (dyskinesia scores, however, showed no less of an improvement).…”
Section: Introductionmentioning
confidence: 99%
“…In de novo patients, Peppe et al [11] did not find superiority of GPi plus STN DBS compared with STN DBS alone. In patients with previous pallidotomy, some authors have even observed a negative interaction, since STN DBS then resulted in more axial symptoms, particularly gait and balance problems [12][13][14]. Other authors, in contrast, did not find a negative influence of previous pallidotomies on subsequent STN DBS efficacy [15].…”
Section: Dear Sirsmentioning
confidence: 99%
“…22,33,38,39 Lentiform nucleus hypermetabolism on FDG-PET (positron emission tomography) scanning also correlates with the response to levodopa and pallidotomy and may correlate with the response to DBS. 40 Therefore, the levodopa test is an important part of the evaluation to determine the degree of benefit obtainable with surgery.…”
Section: Parkinson Diseasementioning
confidence: 99%